(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2016)
The University of Saskatchewan conducted an institutional self-assessment survey in the fall of 2013 and winter of 2014 to measure its capacity for community-engaged scholarship. This effort is part of a national initiative of eight Canadian universities (Community-Engaged Scholarship Partnership), working to change institutional policies and practices around community-engaged scholarship. This paper reports on the results of the University of Saskatchewan’s self-assessment survey completed by 159 participants across campus that include administrators, faculty, and professional staff. The participants report that there are strong practices of community-engaged scholarship throughout the University. However, there are also many opportunities to strengthen the support and capacity for community-engaged scholarship. Institutional leadership and support, for example, that is consistent and effective is required at multiple levels (department, college or school, university) in order for community-engaged scholarship to be recognized and rewarded in all academic processes. The University’s Community Engagement and Outreach Office at Station 20 West is one notable exemplar of community-engaged scholarship and practice; it is a good example of how students, faculty, and community are effectively supported in these activities.